The Influence of Personnel Management and Organizational Structure on Personnel Work Effectiveness in The Security Intelligence Unit of The Depok Metro Resort Police - Firman Zakaria Razak; Harries Madiistriyatno; Widya Nengsih (Dinasti International Journal of Management Science, 2026)
The expected objectives of this research are to analyze and determine the influence of personnel management on the effectiveness of personnel work, analyze and determine the influence of organizational structure on the effectiveness of personnel work and analyze and determine the influence of personnel management and organizational structure simultaneously on the effectiveness of personnel work in the Security Intelligence Unit of the Depok Metro Police Resort. Personnel Management has a significant influence on Personnel Work Effectiveness. The results of the partial test (t test) show that the calculated t value is 7.196, greater than the t table of 2.004, the calculated t value of the Organizational Structure variable (X2) is 7.368, greater than the t table of 2.004, Personnel Management and Organizational Structure simultaneously have a significant effect on Personnel Work Effectiveness, F table is 2.77 with a significance level of 0.000 < 0.05. This proves that Personnel Management (X1) and Organizational Structure (X2) together have a positive and significant effect on Personnel Work Effectiveness (Y). The coefficient of determination (R Square) value of 0.898 shows that 89.8% of Personnel Work Effectiveness is influenced by Personnel Management and Organizational Structure, while the remaining 10.2% is influenced by other factors.